KARAKTERISTIK SIFAT KIMIA BIJI KOPI ARABIKA DENGAN BEBERAPA METODA PENGOLAHAN di KABUPATEN SIMALUNGUN PROVINSI SUMATERA UTARA - RETMONO AGUNG WINARNO; Mawar Indah BR Berangin-angin (Agrivet : Jurnal Ilmu-Ilmu Pertanian dan Peternakan (Journal of Agricultural Sciences and Veteriner), 2021)
Coffee in North Sumatra have an important meaning in the socio-economic aspects of people's lives. One of the problems with developing coffee in Simalungun is the low quality of products. Determinants of coffee quality are influenced by geographical indications of the origin of coffee and how the coffee is processed. The purpose of this study was to determine the chemical characteristics of coffee beans produced from several locations in Simalungun Regency, North Sumatra with various coffee processing methods. The material used is red cherry Arabica coffee fruit taken from several locations, namely Raya District, Purba District and Dolok Pardamean District, with a variety of processing methods (dry method, semi-wash method, full-wash method, and honey method). The observed parameters where the chemical characteristics of coffee bean, including water content, caffeine content, ash content, and free fatty acid content. The results showed that the characteristics of the chemical properties of coffee beans produced by various processing methods were not different. Caffeine levels of coffee beans ranged from 7808.71 mg / kg the lowest to the highest 10422.11 mg / kg. Ash content ranged from 3.71%, the lowest to the highest 4.4%. Free fatty acid content from three district an average was 0.06%.